Evaluation of basal hormone levels and androgen receptor gene mutations in individuals with recurrent abortion - Huang, Xueqin; Ju, Hairong; Song, Guohua (Cellular and Molecular Biology, 2022)
A recurrent miscarriage is at least two consecutive miscarriages in the first trimester of pregnancy. Due to the dependence of pregnancy on endocrine changes in the menstrual cycle, its disorders can also affect the outcome of pregnancy. In addition to hormonal disorders, genetic changes are essential factors in recurrent miscarriage. The development and maturation of ovulation depend on the molecular signaling pathways that respond to androgens. Hundreds of mutations leading to resistance to androgen receptor (AR) gene function have been recorded, including the 5’UTR polymorphic region. Therefore, considering the role of androgen receptors and hormonal changes in recurrent miscarriage, this study was performed to investigate the relationship between hormonal changes and AR gene mutations in patients with recurrent miscarriage. In this regard, a case-control study was performed on 150 patients with miscarriage referred to the infertility center. Hysterosalpingography, parental karyotype, vaginal ultrasound, antiphospholipid antibody measurement, anticardiolipin antibody, history and physical examination were performed to evaluate the possible causes of recurrent miscarriage. Hormone levels of LH, FSH, TSH, and Prolactin were measured and compared in two groups with known and unknown causes. Blood samples were also taken from patients, and after DNA extraction, the PCR method was used to determine AR gene mutations. The mean age was 30.2 ± 7.1 years, the mean number of abortions was 2.6 ± 1.2, and the mean duration of marriage was 6.1 ± 2.1 years. The mean of hormones in the two groups with known and unknown causes was compared, that TSH was significantly lower in the group with unknown cause (P = 0.031) and prolactin was higher in recurrent miscarriage patients with polycystic ovaries (P = 0.048). Regarding genetic evaluation, in the 5’UTR region of the androgen receptor gene, deletion of T nucleotide was observed in the +25 position, but no significant difference was found between the two groups. Generally, the findings of this study showed that thyroid dysfunction and hyperprolactinemia should be considered as an endocrine disorder in people with recurrent miscarriage, and genetic evaluation showed that the AR gene mutation was not associated with recurrent miscarriage.